Benthic macrofauna associated with roots of Rhizophora mangle in the Ciénaga de La Palmita, Maracaibo System, Venezuela - Lárez-Rodríguez, Luis (2023)
The immersed roots of red mangrove constitute a substrate where a variety of invertebrates breed and feed, being one of the most productive tropical ecosystems. With the objective of studying the benthic macrofauna attached to Rhizophora mangle roots in the wetland Ciénaga de La Palmita, 8 stations were sampled in May 2018; the two roots extracted from each station were placed in plastic bags and fixed with 10% formalin. Water temperature, depth, salinity, and transparency were measured. In the laboratory, each root was washed and scraped superficially, and the invertebrates were retained in a 425 µm sieve and preserved in 70% alcohol. Specimens were quantified and identified by taxonomic keys. A total of 27,014 individuals were quantified, with three Phyla identified: Arthropoda, Annelida, and Mollusca, distributed in six classes, 13 orders, 19 families, and 20 species. Crustaceans represented 93.6% of the composition, followed by annelids (3.3%), mollusks (1.6 %), and hexapods (1.5%). Total richness was 20 species. The constancy index yielded 14 constant species, 3 accessory and 3 accidental. The Shannon-Wienner index varied, finding greater diversity in station 4 (H' = 2.01). The cirripede Balanus amphitrite was the dominant species, followed by the tanaidacean Sinelobus stanfordi and the amphipod Americorophium sp., estuarine species adapted to tropical areas. Physicochemical parameters indicate that this is an environment with little fluctuation and low salinity, where marine species and estuarine species converge, presenting a low proportion and richness of mollusks and a high proportion and abundance of crustaceans.